Skeletal muscle dysfunction and oxidative stress in patients with chronic obstructive lung disease - Shuji Oh-ishi; Kenji Nemoto; Takefumi Saito (Japanese Society of Physical Fitness and Sports Medicine, 2015)
Chronic obstructive pulmonary disease (COPD) is an increasingly important global health problem, including Japan. COPD is associated with an enhanced inflammatory response to irritants in the airways and lungs, in particular cigarette smoke. Cigarette smoke contains gaseous and particulate oxidants, and is considered to be the major etiological factor in the development of COPD. The oxidants in cigarette smoke induce inflammation, and chronic inflammation causes narrowing of the small airways and destruction of the lung parenchyma. Inflammation and oxidative stress are intricately related and seem to play a critical role in the development and/or progression of COPD. There is growing evidence that systemic inflammation exists in patients with stable COPD, leading to extra-pulmonary manifestations including skeletal muscle dysfunction and other comorbidities. Oxidative stress is also observed in skeletal muscle of COPD patients. Therefore, both systemic inflammation and oxidative stress may be associated with skeletal muscle dysfunction in COPD patients, resulting in reduced limb muscle strength and exercise endurance and poor health status and quality of life. Pulmonary rehabilitation is important to improve exercise capacity and health-related quality of life for COPD patients. However, physical exercise, the main component of pulmonary rehabilitation, may increase oxidative stress in the skeletal muscle of such patients. Therefore, rehabilitation programs that not only improve exercise capacity and quality of life, but also reduce exercise-induced oxidative stress should be established in the future.